Wit and Vivacity in Jane Austen's PRIDE AND PREJUDICE - Setyabudi, Titis (Journal of English and Education (JEE), 2007)
The main problem of this research is to prove wit and vivacity in Jane Austen’s in Pride and Prejudice. To solve the problem the researcher applies structuralism approach in this study. This approach is used in order to find the wit and vivacity through character’s traits. They are physical trait, social trait and psychological trait.